2013
DOI: 10.1371/journal.pone.0053775
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Behavioral Deficits in Rats during a Cycle of Demyelination-Remyelination of the Fimbria

Abstract: Traumatic brain injury (TBI) selectively damages white matter. White matter damage does not produce deficits in many behavioral tests used to analyze experimental TBI. Rats were impaired on an active place avoidance task following inactivation of one hippocampal injection of tetrodotoxin. The need for both hippocampi suggests that acquisition of the active place avoidance task may require interhippocampal communication. The controlled cortical impact model of TBI demyelinates midline white matter and impairs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The widespread white matter injury in the CHI-2 group of mice is the likely cause of the substantial deficits on the active place avoidance task (Figs 3 – 5 ). We previously showed that rats with localized demyelination of the fimbria do not acquire the active place avoidance task [ 9 ]. The fimbria of the CHI-1 mice had similar silver and LFB staining as the sham-CHI group ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread white matter injury in the CHI-2 group of mice is the likely cause of the substantial deficits on the active place avoidance task (Figs 3 – 5 ). We previously showed that rats with localized demyelination of the fimbria do not acquire the active place avoidance task [ 9 ]. The fimbria of the CHI-1 mice had similar silver and LFB staining as the sham-CHI group ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral deficits, however, did arise using an active place avoidance task after a single closed head impact. The deficits on the active place avoidance task that arose after a single impact likely result from a need for both hippocampi and their commissural connections to acquire the task [ 9 , 10 ]. TBI models frequently damage the hippocampi and their commissural connections.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the demyelination induced by CPZ in the current study and in some previous studies might not be able to induce the spatial learning and working memory impairment. The spatial learning and memory ability might rely less on the communication between two brain regions (coordination by white matter) and more on other brain structures (Grin'kina et al, ). In a future study, we will investigate demyelination changes in more brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Improved cognitive function due to gangliosides [ 5 , 27 ] and phospholipids [ 28 ] could also be mediated through promoting myelination. However the supplementation of BSC did not alter the myelin density in all the brain regions examined.…”
Section: Discussionmentioning
confidence: 99%